2016
DOI: 10.1002/anie.201607867
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium(III)‐Catalyzed Alkenylation–Annulation of closo‐Dodecaborate Anions through Double B−H Activation at Room Temperature

Abstract: 1,2,3-Trisubstituted closo-dodecaborates with B-O, B-N, and B-C bonds as well as a fused borane oxazole ring have been synthesized by rhodium-catalyzed direct cage B-H alkenylation and annulation of ureido boranes in the first reported example of regioselective B-H bond functionalization of the [B H ] cage by transition-metal catalysis. This reaction proceeded at room temperature under ambient conditions and exhibited excellent selectivity for efficient monoalkenylation with good functional-group tolerance. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(33 citation statements)
references
References 63 publications
5
27
0
1
Order By: Relevance
“…The strongest IR peak at 1532 cm −1 (experimentally at 1537 cm −1 ) arises from the involvement of C‐O stretching and N‐H bending, combined with the CH 2 wagging vibration, while the neighboring medium band at 1557 cm −1 (experimentally at 1573 cm −1 ) is mainly dominated by the C‐N stretching vibration. It is noteworthy that, the B‐H‐Rh vibrations (involving the B‐H stretching and Rh‐H bending) can be theoretically found at 2031 cm −1 and experimentally at 2084 cm −1 , and the deviation of 53 cm −1 should ascribe to the influence of measure conditions, for example, experimentally as a KBr pellet and dry film . Conversely, the strong IR band at 2504 cm −1 corresponds to the B‐H stretching vibrations, which is consistent with previously experimental study, located at 2514 cm −1 .…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…The strongest IR peak at 1532 cm −1 (experimentally at 1537 cm −1 ) arises from the involvement of C‐O stretching and N‐H bending, combined with the CH 2 wagging vibration, while the neighboring medium band at 1557 cm −1 (experimentally at 1573 cm −1 ) is mainly dominated by the C‐N stretching vibration. It is noteworthy that, the B‐H‐Rh vibrations (involving the B‐H stretching and Rh‐H bending) can be theoretically found at 2031 cm −1 and experimentally at 2084 cm −1 , and the deviation of 53 cm −1 should ascribe to the influence of measure conditions, for example, experimentally as a KBr pellet and dry film . Conversely, the strong IR band at 2504 cm −1 corresponds to the B‐H stretching vibrations, which is consistent with previously experimental study, located at 2514 cm −1 .…”
Section: Resultssupporting
confidence: 91%
“…The harmonic vibrational frequencies of the RhCD complex were evaluated using theoretical calculations at the B3LYP/def‐SVP level of theory, and a scaling factor of 0.96 was applied to assign well the experimental IR spectrum. In Figure , the calculated and experimental IR spectra are compared, and it is found that the calculated IR spectrum is in good agreement with the experimental observation, from the previous report …”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…Metal-catalyzed transformations will likely emerge in the future targeting synthesis of these molecules. 172 Significantly, many opportunities can be envisioned that stem directly from the ability to generate complex structures that contain multiple functional groups appended to its vertices ( vide supra ). Beyond metal-based catalysis, several studies indicate that perhalogenated carboranes and boron clusters can undergo substitution at B–Cl and B–F vertices, 173,174 suggesting it should be possible to design more well-behaved reaction protocols for creating vertex-differentiated systems via this relatively unexplored pathway.…”
Section: Outlook and Conclusionmentioning
confidence: 99%